Ureteral urothelial carcinoma with squamous cell carcinoma and sarcomatoid carcinoma differentiation: a case report - Shangqing Ren; Hualin Feng; Yige Bao; Yi Wei; Yong Ou; Yaoqian Wang; Qian Lv; Shan Zhong; Fang Zhou; Shida Fan; Qiang Wang; Cheng Luo; et al. (BMC Surgery, 2021)
Abstract Background Upper urinary tract urothelial carcinoma (UTUC) with multiple pathological types is extremely rare in the clinic, but the recurrence rate and mortality these patients are high. At present, there is no standard treatment for such cases. Case presentation We reported a case of ureteral urothelial carcinoma with squamous cell carcinoma and sarcomatoid carcinoma differentiation and rapid ileal metastasis and reviewed the literature related to different pathological types of upper urinary tract tumours to explore the diagnosis, treatment and prognosis characteristics of the disease, enhance our understanding of its clinical manifestations and history of evolution and provide guidance for avoiding missed diagnosis and misdiagnosis. Conclusion There is no standard treatment for urinary malignant tumours with multiple pathological types; radical surgery is considered a suitable choice. Chemotherapy, targeted drug therapy and immunotherapy may be beneficial to the survival of patients. In short, these patients have a high risk of recurrence and metastasis and a poor prognosis.